Pengaruh Pengetahuan Tentang Bank Syariah dan Literasi Keuangan terhadap Minat Menabung Mahasiswa Perbankan Syariah UIN Syahada Padangsidimpuan - Ya’ti Ikhwani Nasution; Haidir Harianja (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
The low understanding of knowledge about Islamic banking and financial literacy, the lack of socialization carried out by Islamic banks on Islamic economic principles and systems can affect the interest in saving for Islamic banking students at UIN Syahada Padangsidimpuan Islamic banking. The discussion in this study relates to Islamic banks, knowledge of Islamic banks, financial literacy and student interest in saving. The type of research used is quantitative research, while the information needed by researchers is obtained directly from the object of research by distributing questionnaires to respondents. The data collection technique used by the researcher is the method of questionnaire (questionnaire), documentation, and interviews. The analysis technique used is the validity and reliability test of the instrument then the data analysis used is the basic assumption test, classical assumption test and hypothesis testing using SPSS 22 computer program data processing. The results of the study simultaneously and partially state that there is an influence between the knowledge and literacy variables. finance on interest in saving Islamic banking students at UIN Syahada Padangsidimpuan by 24.1% and the remaining 75.9% is influenced by other variables.